CARBOXYLATO ADDUCTS AND DERIVATIVES CONTAINING SnR3 (R = Ph, Me) AND SnMe2 RESIDUES: SYNTHESIS, INFRARED AND MÖSSBAUER STUDIES - SEYDOU BASSENE; MOUHAMADOU SEMBENE BOYE; MAMADOU SIDIBE; LIBASSE DIOP (Journal of Engineering Studies and Research)
Twelve new carboxylato adducts and derivatives containing SnR3 (R = Ph, Me) and SnMe2 residues have been synthesized and characterized by elemental analyses, infrared and 119Sn-Mossbauer spectroscopies. The proposed structures are discrete or of infinite chain type, the carboxylate anion behaving as a bridging bidentate, a monodentate, a tetradentate or a monochelating ligand.